RESEÑA de : Caamaño Domínguez, Francisco; Gómez Montoso, Ángel; Medina Guerrero, Manuel y Requejo Pagés, Juan Luis. Jurisdicción y procesos constitucionales. Madrid: McGrawHill, 1997 - Goig Martínez, Juan Manuel (Teoría y Realidad Constitucional, 1999)
-